Gastrointestinal Involvement in Children with Systemic Lupus Erythematosus - Angela Mauro; Teresa Giani; Clelia Di Mari; Martina Sandini; Antonella Talenti; Valentina Ansuini; Luigi Biondi; Giovanni Di Nardo; Luca Bernardo (MDPI AG, 2023)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disorder. When it presents before the age of 18 years (childhood-onset systemic lupus erythematosus, cSLE), the disease course tends to be more severe with a higher rate of organ involvement and requires an early diagnosis. Gastrointestinal involvement in cSLE is rare and scarcely reported in the literature. Any organ of the gastrointestinal system may be affected, either as a direct consequence of the disease, as a subsequent complication, or as an adverse drug event. Abdominal pain is the most common GI symptom, it can be diffuse or well localized, and can underline different conditions such as hepatitis, pancreatitis, appendicitis, peritonitis, or enteritis. cSLE may have an alteration of the intestinal barrier with features of protein-losing enteropathy or, in genetically predisposed patients, may develop associated autoimmune disorders such as Coeliac Disease or Autoimmune Hepatitis. The aim of this manuscript is to provide a narrative review of gastrointestinal manifestations in cSLE focused on hepatic, pancreatic, and intestinal involvement. A comprehensive literature search based on the PubMed database was performed.